The c.64_80del SMIM1 allele is segregating in the Hutterite population. Issue 4 (15th December 2015) - Coghlan, Gail; Zelinski, Teresa
Abstract : BACKGROUND: The high‐incidence red blood cell (RBC) antigen Vel is coded by SMIM1 (small‐membrane molecule 1 gene), where a homozygous 17 base pair deletion underlies the majority of Vel− phenotypes. Because anti‐Vel has been reported to cause severe hemolytic transfusion reactions and periodically hemolytic disease of the newborn and fetus, identification of individuals negative for Vel is clinically important. STUDY DESIGN AND METHODS: RBCs from the members of a large three‐generation Hutterite family were serologically determined to be Vel+ w . Genomic DNA from these family members was polymerase chain reaction amplified and analyzed for SMIM1 polymorphisms by either Sanger sequencing or restriction fragment length polymorphisms. SMIM1 genotyping was also conducted on DNA from an additional 104 Hutterites. RESULTS: All family members whose RBCs weakly expressed the Vel antigen were found to be heterozygous for the c.64_80del mutation in SMIM1 . Of the 104 additional Hutterite samples, four were found to be heterozygous for the same SMIM1 mutation. CONCLUSION: After emigrating to the United States and Canada, the Hutterite population has expanded dramatically. Alleles that initially entered the population have been maintained within the population. The c.64_80del null allele of SMIM1 is one such allele, thus having implications for transfusion medicine and child or maternal health.